Analisis Kemampuan Menulis Teks Narasi Siswa Kelas V SD N Ketiwijayan - Dias Hasna Sukmadewi; Muhardila Fauziah (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the ability to write narrative texts of fifth grade students of SD N Ketiwijayan with qualitative methods through interviews, observations, and document analysis. narrative text is a form of writing that tells an event or incident by prioritizing the role of characters, arranged chronologically to provide a complete explanation or story, and aims to enrich the understanding of readers or listeners through a systematic sequence of time The results show that most students have good narrative writing skills, but there are still some who need improvement, especially in terms of spelling, punctuation, and sentence structure. Out of 13 students, 8 students have good writing skills, 3 students have sufficient skills, and 2 other students have poor skills. Common errors include the use of capital letters and sentence structure which still need to be improved.